Prognostic immunological implications of OX40L expression in the tumor microenvironment of melanoma - Feldman, Susanna; Da’ana, Baseem; Ofek, Nona; Elkis, Liliana; Pollak-Moseri, Adi; Riklin-Nahmias, Emmanuela; Mendlovic, Sonia; Avraham, Ayelet; Leibowitz, Raya (Frontiers in Immunology, 2026)
BackgroundImmunotherapy targeting immune checkpoint proteins (ICPs) has transformed cancer care, yet current treatments focus on a narrow set of inhibitory ICPs and benefit only a subset of patients. The co-stimulatory pair OX40–OX40L, implicated in inflammation and autoimmunity, also plays roles in cancer immunity. We previously showed that high OX40L mRNA expression in melanoma correlates with favorable prognosis and improved responses to PD-1 blockade. However, the protein-level expression and functions of OX40L in melanoma remain poorly defined.MethodsFormalin-fixed paraffin-embedded primary tumor samples from 30 patients with stage II–III melanoma were analyzed by multiplex immunofluorescence combined with quantitative image analysis. OX40L and OX40 expression were evaluated alongside immune cell phenotyping markers. Regulatory T cells (Tregs) isolated from human peripheral blood were examined by flow cytometry and RT-qPCR. Associations with recurrence were assessed in depth-matched subsets (n=22) using Kaplan–Meier analysis.ResultsOX40L was detected across tumor, immune, and stromal compartments, with marked intertumoral heterogeneity. OX40+ cells were less frequent but were often found in spatial proximity to OX40L+ cells. OX40L was infrequently detected in melanoma cancer cells, and was more prevalent in antigen-presenting cells, CD4+/CD8+ T cells, and regulatory T cells. Strikingly, intratumoral Tregs expressed OX40L more frequently than OX40 or other ICPs, whereas blood-derived Tregs showed the opposite pattern, with OX40 predominating over OX40L. Disease recurrence following resection of the primary tumor was associated with lower proportions of OX40L-expressing myeloid cells, providing preliminary evidence for a potential link between myeloid OX40L expression and recurrence risk.ConclusionsOX40L protein expression is a heterogeneous but prominent feature of the melanoma microenvironment, with cell type–specific expression patterns that include regulatory T cells. An exploratory association was seen between myeloid OX40L expression and clinical outcome, warranting further investigation.